2018
DOI: 10.1136/svn-2017-000137
|View full text |Cite
|
Sign up to set email alerts
|

Stenting for symptomatic intracranial arterial stenosis in China: 1-year outcome of a multicentre registry study

Abstract: Background and purposeA multicentre prospective registry study of individually tailored stenting for a patient with symptomatic intracranial atherosclerotic stenosis (ICAS) combined with poor collaterals in China showed that the short-term safety and efficacy of stenting was acceptable. However, it remained uncertain whether the low event rate could be of a long term. We reported the 1-year outcome of this registry study to evaluate the long-term efficacy of individually tailored stenting for patients with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 21 publications
4
33
1
Order By: Relevance
“…Details of the registry have been published elsewhere. [19][20][21] Approval by each site's institutional review board or ethics committee was obtained. Written informed consent was obtained from the patients or their legally authorized representatives.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Details of the registry have been published elsewhere. [19][20][21] Approval by each site's institutional review board or ethics committee was obtained. Written informed consent was obtained from the patients or their legally authorized representatives.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…In a recent Chinese sICAS Registry (NCT01968122),22 all participants were enrolled for hypoperfusion aetiology with poor collaterals within 90 days after onset, and received individualised endovascular treatment. Patients had 4.3% and 8.1% of stroke recurrence at 30 days and 1 year, respectively,22 23 which is quite lower than in the SAMMPRIS Trial. Despite ethnic differences between various trials, we believe that the results of the Chinese Trial were better mainly due to the highly selective patient enrolment.…”
mentioning
confidence: 70%
“…These both demonstrated approximately 6% periprocedural complication rate and represented the initial clinical experience with the stent in the USA. Subsequent large clinical series were reported by multiple centres in both single-centre registries and multicentre trials 29–36…”
Section: Endovascular Therapy: Intracranial Stentingmentioning
confidence: 99%
“…Following SAMMPRIS, there have been several single-centre and multicentre trials and registries that have demonstrated much safer periprocedural results with the Wingspan stent, provided that the time to treatment was delayed 2–3 weeks following the last stroke 29–36. In a multicentre trial comparing a balloon-expandable stent with the Wingspan self-expanding stent in over 300 patients, Ma et al 34. demonstrated a 4% periprocedural complication rate, and a total 1-year follow-up stroke, TIA, bleed and death rate of 7.9% in the Wingspan-treated group.…”
Section: Endovascular Therapy: Intracranial Stentingmentioning
confidence: 99%